(untitled) - Hacker, Diana (Boston, 2007)
Our best selling classic tabbed handbook is available in a version that conveniently includes nearly one hundred integrated exercise sets for plenty of practice with the grammar, style, punctuation, and mechanics topics offered in the handbook. The answers to lettered items appear in the back of the book.
Keywords: English language,Tiếng Anh; Rhetoric,Handbooks, manuals, etc.,Kỹ năng nói,Sổ tay v, hướng dẫn sử dụng, vv